B-cell-depleted patients with persistent SARS-CoV-2 infection: combination therapy or monotherapy? A real-world experience - D’Abramo, Alessandra; Vita, Serena; Beccacece, Alessia; Navarra, Assunta; Pisapia, Raffaella; Fusco, Francesco Maria; Matusali, Giulia; Girardi, Enrico; Maggi, Fabrizio; Goletti, Delia; Nicastri, Emanuele; , ImmunoCOVID team; et al. (Frontiers in Medicine, 2024)
Abstract Objectives The aim of the study was to describe a cohort of B cell-depleted immunocompromised (IC) patients with prolonged or relapsing COVID-19 treated with mono- or combined-therapy. Methods This is a multicentre observational retrospective study conducted on IC patients consecutively hospitalized with prolonged or relapsing SARS-CoV-2 infection from November 2020 to January 2023. IC COVID-19 subjects were stratified according to the mono or combination anti-SARS-CoV-2 therapy received. Results Eighty-eight patients were enrolled, 19 under monotherapy and 69 under combined therapy. All study population had a history of immunosuppression (median of 2 B cells/mm3, IQR 1-24 cells) and residual hypogammaglobulinemia was observed in 55 patients. A reduced length of hospitalization and time to negative SARS-CoV-2 molecular nasopharyngeal swab in combined versus monotherapy group was observed. On univariable and multivariable analysis, the percentage change in the rate of days to nasopharyngeal swab negativity showed a significant reduction in patients receiving combination therapy compared to those receiving monotherapy Conclusions In IC persistent COVID-19 patients it is essential to explore new therapeutic strategies such as combined multi-targets therapy (antiviral or double antiviral plus antibody-based therapies) to avoid persistent viral shedding and/or severe SARS-CoV-2 infection.